2014
DOI: 10.1590/0103-8478cr20131150
|View full text |Cite
|
Sign up to set email alerts
|

Elaboração e implantação do sistema de análise de perigos e pontos críticos de controle no processamento de leite pasteurizado tipo A

Abstract: RESUMO A análise de perigos e pontos críticos de controle (APPCC) é uma das principais ferramentas utilizadas atualmente para a garantia da inocuidade, qualidade e integridade dos alimentos. O objetivo deste trabalho foi elaborar e implantar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…The literature review allowed the analysis of the existing instruments and methods, as well as the theoretical basis for the decision and elaboration of a new instrument. Following the identification of primary sources, review of secondary sources, critical reading and summary of the literature was performed using keywords or descriptors: risk, health risk, epi-demiological risk, potential risk, health surveillance, health inspection, food health inspection, health inspection roadmap, health inspection in restaurants roadmap, industrial kitchen health inspection roadmap, health inspection validation, questionnaires, evaluation instruments, and elaboration and validation of instrument 21,[23][24][25][26][27][28] .…”
Section: Elaboration Of the Iqismentioning
confidence: 99%
“…The literature review allowed the analysis of the existing instruments and methods, as well as the theoretical basis for the decision and elaboration of a new instrument. Following the identification of primary sources, review of secondary sources, critical reading and summary of the literature was performed using keywords or descriptors: risk, health risk, epi-demiological risk, potential risk, health surveillance, health inspection, food health inspection, health inspection roadmap, health inspection in restaurants roadmap, industrial kitchen health inspection roadmap, health inspection validation, questionnaires, evaluation instruments, and elaboration and validation of instrument 21,[23][24][25][26][27][28] .…”
Section: Elaboration Of the Iqismentioning
confidence: 99%
“…It is assumed that the milk processing chain in this country still needs improvement. Tobias, Ponsano and Pinto (2014) concluded that the implementation of Good Manufacturing Practices together with the hazards control and critical control points in the pasteurized milk processing in Brazil is the key to significant reduction of microorganisms, achieving a 20% reduction in the values found before implementation, being the main tool used currently to ensure safety, quality and integrity of the pasteurized milk.…”
Section: Resultsmentioning
confidence: 99%
“…Diante desse quadro, o sistema APPCC, associado aos PPR, tem se mostrado como ferramenta básica do sistema vigente de controle da qualidade nas indústrias de alimentos, certificando a segurança dos produtos, diminuindo custos e expandindo a lucratividade, por meio da redução das perdas e do retrabalho. Além disso, essas ferramentas da qualidade aprimoram processos e torna dispensável boa parte das análises laboratoriais executadas no sistema de controle de qualidade tradicional, transformando o processo de controle veraz e seguro (Ribeiro-Furtini & Abreu, 2006;Tobias, Ponsano & Pinto, 2014).…”
Section: Introductionunclassified